2011
DOI: 10.1097/ccm.0b013e3181feb824
|View full text |Cite
|
Sign up to set email alerts
|

Postintensive care unit psychological burden in patients with chronic obstructive pulmonary disease and informal caregivers: A multicenter study

Abstract: Psychiatric symptoms were found to be common in a group of 126 patients with chronic obstructive pulmonary disease who survived an intensive care unit stay and their relatives at intensive care unit discharge and 90 days later. Peritraumatic dissociation at intensive care unit discharge was found to independently predict posttraumatic stress disorder-related symptoms in this sample of patients and relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 58 publications
4
107
0
4
Order By: Relevance
“…A stay in the ICU may also be associated with significant and long-lasting distress; two-thirds of patients remembered their stay in the ICU associated with negative affect and post-traumatic stress [139]. In fact, memories of ''suffocation'' were the second most reported complaint after a stay in the ICU [140]. Things could get worse in the future, as current ICU management trends are designed to reduce iatrogenic complications and shorten ICU stay.…”
Section: Dyspnoea Mechanisms and Relief In Specific Conditionsmentioning
confidence: 99%
“…A stay in the ICU may also be associated with significant and long-lasting distress; two-thirds of patients remembered their stay in the ICU associated with negative affect and post-traumatic stress [139]. In fact, memories of ''suffocation'' were the second most reported complaint after a stay in the ICU [140]. Things could get worse in the future, as current ICU management trends are designed to reduce iatrogenic complications and shorten ICU stay.…”
Section: Dyspnoea Mechanisms and Relief In Specific Conditionsmentioning
confidence: 99%
“…A study including patients with COPD and their relatives after an intensive care unit (ICU) stay showed that 72% of the caregivers had symptoms of anxiety and 26% had symptoms of depression at the point of discharge from the ICU [40]. After 90 days, 32% of the caregivers received medication for anxiety or depression prescribed after the patient's ICU stay [40].…”
Section: Impact On Informal Caregiversmentioning
confidence: 99%
“…A study including patients with COPD and their relatives after an intensive care unit (ICU) stay showed that 72% of the caregivers had symptoms of anxiety and 26% had symptoms of depression at the point of discharge from the ICU [40]. After 90 days, 32% of the caregivers received medication for anxiety or depression prescribed after the patient's ICU stay [40]. In a general population, symptoms of depression were more prevalent in caregivers of nonsurvivors [41], indicating that the burden is higher in caregivers of deceased patients.…”
Section: Impact On Informal Caregiversmentioning
confidence: 99%
“…Symptoms of post-traumatic stress disorder (PTSD), another outcome of concern, have been reported in 35~50% of family caregivers [31][32][33][34]. For the first 6 months after patients' ICU discharge or death, symptoms of PTSD have been reported to be problematic in more than one third of family members [31,32,34].…”
Section: Psychological Outcomesmentioning
confidence: 99%